Bandgap and electronic structure of CaSiN2: Experiment and theory. Issue 1 (3rd August 2022) - de Boer, Tristan; Boyko, Teak D.; Braun, Cordula; Schnick, Wolfgang; Moewes, Alexander
Abstract: We interrogate the electronic properties of the nitridosilicate CaSiN2 as determined using soft X‐ray absorption and emission spectroscopy, which probe directly the partial electronic density of states. We compare our measurements to full potential, all electron density functional theory (DFT) calculations. Good agreement between experiment and theory is obtained, and the electronic bandgap of CaSiN2 is determined to be 3.95 ± 0.3 eV, in contrast with our predicted value of 4.78 eV that was calculated using the modified Becke–Johnson exchange‐correlation functional with the DFT framework.